Phytochemical Screening and Analgesic Activity of Opuntia ficus indica cladods extract in Wistar rats - Sihem HALMI; Madi A; Madi A; Berouel K; Lemoui R; Benlakssira B; Hamdi pacha Y (International Journal of Phytomedicine, 2016)
The purpose of this work is the study of the peripheral and central analgesic activity of the Opuntia ficus indica cladods extract. Different concentrations are tested: 1000 mg/kg; 2000 mg/kg and 3000 mg/kg of body weight on rats by three different methods: the tail flick, the hot-plate and the writhing test to the acetic acid. The results obtained show that the aqueous extract of the cladods has an peripheral and central analgesic activity comparable to that of the Aspirin after administration to rats. The phytochemical analysis of the extract reveals the presence of tannins, coumarins, flavonoids, steroids and anthocyanins whose properties can be used to advantage in the treatment of pain. Our results confirm the traditional use of Opuntia ficus-indica cladods as an analgesic.